Analysis of chemosensory genes in Semiothisa cinerearia reveals sex-specific contributions for type-II sex pheromone chemosensation - Zhu, Xiu-Yun; Xu, Ji-Wei; Li, Lu-Lu; Wang, Dong-Yun; Zhang, Meng-Li; Yu, Nan-Nan; Purba, Endang R.; Zhang, Fan; Li, Xiao-Ming; Zhang, Ya-Nan; Mang, Ding-Ze (Genomics, 2020)
Insects employ a sensitive chemosensory system to accurately recognize external odorants, which help them to make a behavioral response quickly. Semiothisa cinerearia has caused serious damages to Sophora japonica L. in recent years, and there is still a lack of effective strategy to control the pest. Although the two type-II sex pheromones of S. cinerearia, 6Z,9Z-cis-3,4-epoxy-17:H and 3Z,6Z,9Z-17:H, have been identified for 30 years, the molecular mechanisms underlying the chemosensation of the two sex pheromones are still unknown. Here, we found that there are differences in the types of antennae sensilla between sexes, and revealed 146 putative chemosensory genes in the antennal transcriptome. Among these genes, 11 and 40 of them displayed male-biased and female-biased expression, respectively. Our findings greatly improve the chemosensory gene resources for S. cinerearia and provide a foundation for functional studies of these sex-biased genes on the chemosensation of sex pheromones and on other sex-related behaviors. [Display omitted] •There were differences in the types of antennae sensilla between male and female moths of S. cinerearia.•The male and female antennal transcriptome of S. cinerearia were successfully assembled.•We first identified 146 candidate chemosensory genes in S. cinerearia.•We provide a foundation for future studies on the chemosensation of Type-II sex pheromones.